A Free-Standing Electromagnetic Energy Harvester for Condition Monitoring in Smart Grid. (19th February 2021) - Wang, Hao; Shi, Guangyu; Han, Congzheng
Abstract : Wireless energy harvesting is an effective way to power condition monitoring sensors which are the basis of smart grid. In this paper, a new free-standing I-shaped core is designed to scavenge electromagnetic energy from large alternating current. An I-shaped core can guide more magnetic flux by adding a pair of magnetic flux collector plates at both ends of the rod core. It weakens the core demagnetization field and enables more energy to be collected. Since a magnetic field line can be bent with high-permeability soft magnetic materials, a highly efficient grid-shaped coil is proposed. Compared with the I-shaped coil, its weight is lighter and power density is higher. A Mn-Zn ferrite with high relative permeability and ultralow conductivity can effectively reduce eddy current loss, which proves to be the most suitable material. The measured open circuit voltage agrees well with the theoretical value. The experimental results show that the output power can reach 4.5 mW when the I-shaped coil is placed in a magnetic flux density of 6.5 μ Trms . The power density is 7.28 μ W/cm 3 . Therefore, the proposed design can be very effective for supplying condition monitoring sensors.